Patents on Magnetoelectric Multiferroics and their Processing by Electrophoretic Deposition - Mahajan, Amit; V. Ramana, Eskilla (Recent Patents on Materials Science, 2014)
With the evolution of microelectronics, the size of devices is getting smaller and smaller with hybrid functionalities. The thick film technology is becoming more important for miniaturization in the field of electronics to fabricate surface mounted devices, hybrid integrated circuits and sensors. A number of established techniques for thick film fabrication such as screen printing, ink-jetting, tape casting and electrophoretic deposition (EPD) have been reported. Among all the above techniques, electrophoretic technique has gained considerable importance for a variety of applications in view of its high reliability, low cost, high performance and flexibility to produce films with variable thicknesses ranging from hundreds of nanometres to few micro meters. In the last few decades, EPD has been employed as a major fabrication technique for thin/thick films of ferrite, ferroelectric and multiferroic materials for their applications in high frequency, data storage and hybrid functional devices respectively. The review starts with the introduction on multiferroic and magnetoelectrics followed by the fundamental and possible mechanisms as well as some significant results on multiferroic properties of materials. In the application section, patents related to the fabrication and devices have been discussed. In the later part of the review, various aspects of the electrophoretic deposition were discussed for the fabrication of thick composite films. The implementation of EPD for the fabrication of multiferroic and magnetoelectric films was briefed based on literature.
Keywords: electrophoretic deposition